Determinants of Portuguese Banks’ Profitability – An Update - Maria Clara Pires; Maria Basílio; Carlos Borralho (Tourism & Management Studies)
In this study, we assess the main determinants of banks' profitability in Portugal over the period 2015–2018. We divide the factors that can influence bank profitability into several groups: management quality, credit quality, capital adequacy, liquidity (internal bank factors), and GDP growth (an external factor). The panel dataset is composed of annual report data for the 18 major banks operating in Portugal, representing about 98% of the Portuguese banking product. Profitability has been a persistent challenge for banks since the global financial crisis. Moreover, the Portuguese banking system had been facing several structural problems, which makes this topic particularly relevant. The profitability proxy used is the return on equity (ROE). The empirical strategy followed was pooled OLS. Variables relevant for explaining Portuguese banks' profitability are capital adequacy, liquidity and credit risk. As expected, the results show that capital adequacy (TIER 1) and credit quality (CVCT) have a negative and significant impact on banks' profitability, whereas liquidity (RAL) has a positive impact.